Case study: Utilizing Open Education Resources to Enhance Students’ Learning Outcomes during the COVID-19 Schools Lockdown: A Case of Kolibri by Selected Government Schools in Uganda - David Kabugo (Commonwealth of Learning, 2020)
A preview of the international dashboard of trends in education suggests that Open Education Resources (OERs) have and will continue to impact the provision of education during institutional closure owing to the global Covid-19 pandemic. However, the toughest question that is often presented to OERs promoters regards the efficiency (sustainability) and the pedagogical effectiveness of OERs: If education resource users are not cognizant and do not pay for the production, distribution, and utilization of the required resources, then, how can the production, distribution, and utilization of such resources be efficiently and effectively used? Basing on usage-logs and interview data that were collected from 25 teachers in 10 Government-Aided Secondary Schools in Uganda, this report presents a Discourse Analysis of teachers’ use of OERs on Kolibri and draws on such insights gained to propose a potentially transformative model for efficient and effective utilization of OERs to enhance students’ learning outcomes during COVID-19 schools lockdown.